Electronis Discussion
0 votes

$a, b, c$ are real numbers. The quadratic equation $ax^{2}-bx+c=0$ has equal roots, which is $\beta$, then

  1. $\beta =b/a$
  2. $\beta^{2} =ac$
  3. $\beta^{3} =bc/\left ( 2a^{2} \right )$
  4. $\beta^{2} \neq 4ac$
in Numerical Ability by (1.4k points)
edited by

1 Answer

0 votes
In general, for a quaratic equation  $ax^{2}+bx+c=0$ , sum of roots is defined as :  $\frac{-b}{a}$  and product of roots is defined as :  $\frac{-c}{a}$

$\therefore$  Here both the roots are $\beta$.

So,  according to the given quadratic equation , we have  $2\beta=\frac{b}{a}$ ---(1)  and  $\beta^{2}=\frac{c}{a}$-----(2)

Multiplying equations (1) and (2) and simplifying,  we get  $\beta^{3}=\frac{bc}{2a^{2}}$  

Option C is correct
by (260 points)
Welcome to GO Electronics, where you can ask questions and receive answers from other members of the community.
1,109 questions
59 answers
43,381 users